Investigation of selected respiratory effects of (dex)medetomidine in healthy Beagles. (September 2020) - Pleyers, Tekla; Levionnois, Olivier; Siegenthaler, Joëlle; Spadavecchia, Claudia; Raillard, Mathieu
Abstract: Objective: To investigate the effects of sedative doses of intravenous (IV) medetomidine (MED) or dexmedetomidine (DEX) on selected respiratory variables in dogs. Study design: Randomized, blinded, crossover study. Animals: A total of eight healthy adult research Beagles. Methods: Dogs breathing room air had an electrical impedance tomography belt placed around the chest and were maintained in right lateral recumbency. Respiratory rate ( f R ) in movements minute –1 (mpm) and changes in thoracic impedance (ΔZ) in arbitrary units (AU) were recorded for 120 seconds before (T0) and exactly 10 minutes (T10) after the administration of IV DEX (10 μg kg –1 ) or MED (20 μg kg –1 ), with a minimum washout period of 10 days between treatments. Minute ΔZ ( ΔZ ˙ ) was calculated by multiplying median ΔZ with f R . Data are presented as median (interquartile range). Significance for an overall effect of drugs (DEX versus MED) or treatment (T0 versus T10) was quantified with a two-way analysis of variance for repeated measures, followed by, when appropriate, Wilcoxon's signed rank test for each factor. Results: Overall, f R decreased from 26 (22–29) mpm at T0 to 13 (10–21) mpm at T10 ( p = 0.003) and ΔZ increased from 1.133 (0.856–1.599) AU at T0 to 1.650 (1.273–2.813) AU at T10 ( p = 0.007), but ΔZ ˙ did not change [30.375 (23.411–32.445) AU minute –1 at T0 and 30.581 (22.487–35.091) AU minute –1 at T10]. There was no difference between DEX and MED. Most dogs developed a peculiar breathing pattern characterized by clusters of breaths followed by short periods of apnoea. Conclusions and clinical relevance: Both drugs caused a change in breathing pattern, reduction in f R and increase in ΔZ but did not affect ΔZ ˙ . It is likely that (dex)medetomidine resulted in reduction in f R and increase in tidal volume without impacting minute volume.